Peningkatan Keterpaduan Layanan Transportasi Antarmoda pada Kawasan Poris Plawad di Kota Tangerang - Yusuf, Ferdinan; Priyanto, Sigit; Taufik Mulyono, Agus (Politeknik Transportasi Darat Indonesia - STTD Bekasi, 2023)
The integration of intermodal transportation services has become a strategic necessity in improving the quality of urban transportation services, which is reflected in the extent to which the provision of facilities, infrastructure, and supporting amenities can enhance travel experiences and promote sustainable transportation. Achieving integration should focus on major transportation nodes in an area, such as the Poris Plawad Terminal and Batu Ceper Station in the Poris Plawad area of Tangerang City. The Poris Plawad area is also part of the government's plan to develop it as a Transit Oriented Development (TOD) area. This research aims to evaluate the needs and performance of services and determine priorities for improving intermodal transportation services in the Poris Plawad area. The sampling technique used is purposive sampling, with a total of 202 respondents obtained. Data collection from respondents was carried out through questionnaires distributed to transportation service users at the Poris Plawad Terminal and Batu Ceper Station, as well as residents within an 800-meter radius of both transportation nodes. This study uses an integrated approach combining the Importance Performance Analysis (IPA) method and the Kano model. The analysis results indicate that there are 5 service provision needs that need to be prioritized for improvement at present. Firstly, the provision of crossing facilities. Secondly, the provision of connected pedestrian paths (sidewalks). Thirdly, uninterrupted sidewalk functionality. Fourthly, the quality of sidewalk pavements. And fifthly, the access to and from the transportation nodes free from traffic conflicts.